Research advancements in smart technology, optimization, and renewable energy - Vasant, Pandian 1961-; Weber, Gerhard-Wilhelm 1960-; Punurai, Wonsiri 1979- (IGI Global, Publisher of Timely Knowledge, 2021)
"This book explores the recent steps forward for smart applications in sustainability" - Provided by publisher
Keywords: Technological innovations; Smart materials; Artificial intelligence / Industrial applications; Wearable technology; Machine learning; Renewable energy sources; Electric power systems; Aufsatzsammlung